NUMERICAL SIMULATION OF FLOW PARAMETERS THROUGH SUBSURFACE DRAINAGE MODULE SYSTEM - Suleiman, Nur Aqilah (Universiti Teknologi PETRONAS, 2020)
Subsurface drainage module system facilitates the infiltration process of stormwater flows of BIOECODS by increasing the total drainage system surface area. Stormwater flow undergoes double-infiltration through the subsurface module system. This cycle reduces peak flow and build some lag time between peak rainfall and peak flow in the system. Previous hydraulic performance assessments of this system have been conducted by several studies since its debut. However, the assessments show several limitations in terms of time and complexity of the study and lacks comparison element between designs. This study aims to simulate the subsurface modular flows of REDAC and Rainsmart and find out the performance of its flow parameters through the system through numerical simulation using Flow-3D software.